Adaptive predictor control for stabilizing pressure in a managed pressure drilling system under time-delay. (April 2016) - Zhou, Jing; Krstic, Miroslav
Abstract : Highlights: In this paper, we address adaptive predictor feedback design for a simplified ODE drilling system in the presence of unknown parameter, disturbance and time-delay. The main objective is to stabilize the bottomhole pressure at a critical depth at a desired set-point directly. The time-delay in the transmission line of the drilling systems is considered. Through the backstepping transformation in PDE representation, the stabilization of the dynamic system and the asymptotic pressure regulation are demonstrated by the proposed predictor control, where the adaptation employs Lyapunov update law design with normalization. The simulation results show that the proposed predictor controller is effective to stabilize the bottom hole pressure within the desired bound and compensate the effects of the delay in MPD. Abstract: In this paper, we address adaptive predictor feedback design for a simplified ODE drilling system in the presence of unknown parameter, disturbance and time-delay. The main objective is to stabilize the bottomhole pressure at a critical depth at a desired set-point directly. The time-delay in the transmission line of the drilling systems is considered. The stabilization of the dynamic system and the asymptotic tracking are demonstrated by the proposed predictor control, where the adaptation employs Lyapunov update law design with normalization. The proposed method is evaluated using a high fidelity drilling simulator and cases from a North Sea drilling operation are simulated. The results show that the proposed predictor controller is effective to stabilize the bottom hole pressure within the desired bound and compensate the effects of the delay in MPD. The simulation also shows that the proposed method provides good tracking, good disturbance rejection, and good compensation of time-delay.